Recent developments In international mediation: Singapore’s unique approach - HADIKUSUMO, Josephine (Institutional Knowledge at Singapore Management University, 2015)
Singapore’s vibrant dispute resolution sector has been growing on the back of a significant rise in commercial transactions in Asia and a corresponding increase in the number and complexity of cross-border disputes. In particular, Singapore has achieved significant success in the field of international arbitration. Singapore has been recognised as the third most preferred seat of arbitration, after London and Geneva, and the Singapore International Arbitration Centre (“SIAC”) is the fourth most preferred arbitral institution worldwide despite being a relatively young institution. In recent years, Singapore law firms have also ranked amongst the top international arbitration practices in Asia.In order to make Singapore stand out as a premier destination for legal services and resolution of disputes for Asia and the world, the Ministry of Law of Singapore concluded that focus needed to be placed on developing the mediation space, particularly to deal with international commercial disputes, as a complement to arbitration and litigation.